2017
DOI: 10.5377/ceiba.v54i2.3227
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del Hongo Isaria fumosorosea Wize Sobre la Herbivoría por los Adultos del Escarabajo de Margen Amarillo, Microtheca ochroloma Stal (Coleoptera: Chrysomelidae)

Abstract: Resumen. El escarabajo de margen amarillo, Microtheca ochroloma Stål (Coleoptera: Chrysomelidae) es una plaga que causa pérdidas económicas en la producción de crucíferas (Brassicaceae) en Argentina y el sureste de los Estados Unidos. El control biológico utilizando el hongo entomopatógeno Isaria fumosorosea Wize (Hypocreales: Cordycipitaceae) es una alternativa para reducir las poblaciones de esta plaga. Este estudio evaluó el efecto que tiene este hongo en la cantidad de herbivoría por los adultos del escara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Radial growths at day 15 for all EPF subjected to 50% concentration of bok choy and turnip leaf extracts were greater than radial growth on PDA without leaf extract; however, radial growths of C. fumosorosea Apopka strain and B. bassiana GHA strain exposed to the turnip leaf extract were greater at the 25% concentration level (Figure 3). Although interesting, these findings are contrary to what we expected to observe based on a previous in vivo study where the yellowmargined leaf beetle adult was rarely infected by C. fumosorosea Apopka strain while feeding on bok choy leaves sprayed with the fungus [17,18]. However, in corroboration with the findings in our study, Lin et al [41,42] observed that the herbivore-induced plant volatiles (HIPVs) emitted from the crucifer Arabidopsis thaliana (L.) Heynh, while its leaves were fed on by the aphid L. erysimi, were stimulatory to spore germination and appressorial formation of L. lecanii, which are requisites for pathogenicity of the fungal infection.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Radial growths at day 15 for all EPF subjected to 50% concentration of bok choy and turnip leaf extracts were greater than radial growth on PDA without leaf extract; however, radial growths of C. fumosorosea Apopka strain and B. bassiana GHA strain exposed to the turnip leaf extract were greater at the 25% concentration level (Figure 3). Although interesting, these findings are contrary to what we expected to observe based on a previous in vivo study where the yellowmargined leaf beetle adult was rarely infected by C. fumosorosea Apopka strain while feeding on bok choy leaves sprayed with the fungus [17,18]. However, in corroboration with the findings in our study, Lin et al [41,42] observed that the herbivore-induced plant volatiles (HIPVs) emitted from the crucifer Arabidopsis thaliana (L.) Heynh, while its leaves were fed on by the aphid L. erysimi, were stimulatory to spore germination and appressorial formation of L. lecanii, which are requisites for pathogenicity of the fungal infection.…”
Section: Discussioncontrasting
confidence: 99%
“…Although speculative and interesting, this hypothesis requires further study to confirm this specific scenario. However, the yellowmargined leaf beetle was observed to be unaffected by the presence of C. fumosorosea propagules after feeding on bok choy leaf [17,18]. Researchers investigating similar tritrophic interactions have concluded that plant exudates and HIPVs released on the leaf phylloplane can affect: (1) the impact of insect fungal pathogens by enhancing or decreasing persistence on the leaf surface [35,41,46], (2) the encounter rate between the insect and the pathogen [47], (3) insect susceptibility to disease [33,[48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Consumption by the cowpea leaf beetle, Ootheca mutabilis Shalberg, treated with B. bassiana CPD 3 in feeding assays was significantly reduced within 2 days post-treatment, and this trend continued until 7 days when all the beetles died [44]. Most recently, this trend was also observed where the yellowmargined leaf beetle, Microtheca ochroloma Stål, consumption of bok choy leaves treated with Ifr was significantly reduced compared to the untreated plants [45]. …”
Section: Discussionmentioning
confidence: 99%